Effects of an Impulse Frequency Dependent 10-Week Whole-body Electromyostimulation Training Program on Specific Sport Performance Parameters. - Berger, Joshua; Ludwig, Oliver; Becker, Stephan; Backfisch, Marco; Kemmler, Wolfgang; Fröhlich, Michael (Journal of Sports Science and Medicine, 2020)
The difference in the efficacy of altered stimulation parameters in whole-body-electromyostimulation (WB-EMS) training remains largely unexplored. However, higher impulse frequencies (>50 Hz) might be most adequate for strength gain. The aim of this study was to analyze potential differences in sports-related performance parameters after a 10-week WB-EMS training with different frequencies. A total of 51 untrained participants (24.9 ± 3.9 years, 174 ± 9 cm, 72.4 ± 16.4 kg, BMI 23.8 ± 4.1, body fat 24.7 ± 8.1 %) was randomly divided into three groups: one inactive control group (CON) and two training groups. They completed a 10-week WB-EMS program of 1.5 sessions/week, equal content but different stimulation frequencies (training with 20 Hz (T20) vs. training with 85 Hz (T85)). Before and after intervention, all participants completed jumping (Counter Movement Jump (CMJ), Squat Jump (SJ), Drop Jump (DJ)), sprinting (5m, 10m, 30m), and strength tests (isometric trunk flexion/extension). One-way ANOVA was applied to calculate parameter changes. Post-hoc least significant difference tests were performed to identify group differences. Significant differences were identified for CMJ (p = 0.007), SJ (p = 0.022), trunk flexion (p = 0.020) and extension (p=.013) with significant group differences between both training groups and CON (not between the two training groups T20 and T85). A 10-week WB-EMS training leads to significant improvements of jump and strength parameters in untrained participants. No differences could be detected between the frequencies. Therefore, both stimulation frequencies can be regarded as adequate for increasing specific sport performance parameters. Further aspects as regeneration or long term effects by the use of different frequencies still need to be clarified.
EVALuna2:420615